2004
DOI: 10.1007/s00259-004-1598-6
|View full text |Cite
|
Sign up to set email alerts
|

11C-methionine PET as a prognostic marker in patients with glioma: comparison with 18F-FDG PET

Abstract: Compared with FDG PET in glioma, MET PET was an independent significant prognostic factor and MET uptake was correlated with cellular proliferation. MET PET may be a useful biological prognostic marker in glioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 22 publications
4
81
1
2
Order By: Relevance
“…Therefore, natural or artificial amino acid analogs have been widely studied clinically as potential post-FDG radiopharmaceuticals for PET imaging; One of the most important radiolabeled amino acids in this regard is [S-methyl-11 C]-L-methionine ([ 11 C]MET) [6,7]. Since both amino acid transport and protein synthesis rates are enhanced in tumors, [ 11 [8,9].…”
Section: -[ 18 F]fluoro-2-deoxy-d-glucose ([ 18 F]fdg)mentioning
confidence: 99%
“…Therefore, natural or artificial amino acid analogs have been widely studied clinically as potential post-FDG radiopharmaceuticals for PET imaging; One of the most important radiolabeled amino acids in this regard is [S-methyl-11 C]-L-methionine ([ 11 C]MET) [6,7]. Since both amino acid transport and protein synthesis rates are enhanced in tumors, [ 11 [8,9].…”
Section: -[ 18 F]fluoro-2-deoxy-d-glucose ([ 18 F]fdg)mentioning
confidence: 99%
“…These 2 novel approaches offer benefits for glioma resection, and combining these approaches in glioma surgery is rational. However, limited information is available regarding the relationship between 11 C-methionine uptake and 5-ALA-induced PPIX accumulation in glioma tissues. Moreover, only limited information has been reported on the tumor characteristics correlating with each of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…17 Image-guided resection with PET images has thus become important in cytoreduction surgery for glioma. In particular, increasing evidence suggests the utility of 11 C-methionine PET for the purpose of delineating the tumor invasion area. 5 On the other hand, fluorescence-guided resection using 5-aminolevulinic acid (5-ALA) has been developed to achieve the same goal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one biochemical analysis, 11 C-methionine uptake was reported to reflect both protein synthesis in tumor cells and amino acid transport in tumor endothelial cells [16]. Several reports have suggested that 11 C-methionine uptake measured with PET reflects the proliferative index of gliomas [17,18] and microvessel density of tumor tissue, putative markers of protein synthesis and amino acid transport through microvessels, respectively [19].…”
Section: Introductionmentioning
confidence: 99%